Stagonospora nodorum: cause of stagonospora nodorum blotch of wheat - Solomon, P.; Lowe, R.; Tan, Kar-Chun; Waters, O.; Oliver, Richard (Wiley-Blackwell Publishing Ltd., 2006)
Stagonospora nodorum is an important pathogen of wheat and related cereals, causing both a leaf and glume blotch. This review summarizes recent advances in our understanding of taxonomy, control and pathogenicity of this species. Taxonomy: Stagonospora (syn. Septoria ) nodorum (Berk.) Castell. and Germano [teleomorph: Phaeosphaeria (syn. Leptosphaeria ) nodorum (Müll.) Hedjar.], kingdom Fungi, phylum Ascomycota, subphylum Euascomycota, class Dothideomycetes, order Pleosporales, family Phaeosphaeriaceae, genus Phaeosphaeria , species nodorum . Host range: Wheat, Triticum aestivum , T. durum , Triticale, are the main hosts but other cereals and wild grasses have been reported to harbour S. nodorum. Disease symptoms are lens-shaped necrotic lesions on leaves, girdling necrosis on stems (especially the nodes, hence ‘ nodorum ’ ) and lesions on glumes. Mature lesions produce pycnidia scattered throughout the lesions, especially as tissue senesces. Useful websites: http://ocid.nacse.org/research/deephyphae/ htmls/asco_taxlist_spat.html (taxonomic information), http://ohioline.osu.edu/ac-fact/0002.html (disease information), http://wwwacnfp.murdoch.edu.au/ (ACNFP homepage), http://www.broad.mit.edu/annotation/fungi/stagonospora_nodorum/ index.html (genome sequence homepage), http://cogeme.ex.ac.uk/efungi/ (genome sequence annotation and analysis).